The defence of territory and local struggle for more democracy in post-war Guatemala. Issue 5 (4th July 2018) - Illmer, Patrick
ABSTRACT: Twenty years since the signing of the Peace Accords, shifts have taken place in Guatemala's landscape of collective struggles for democracy. Instead of the historical peasant movements or the civil society organizations based in Guatemala City that dominated collective action in the context of the Accords, over the past decade local, rural nodes of resistance to neo-liberal policies have consolidated as the most sustained attempts to instil a democratizing impetus. In the context of Guatemala's post-war state, captured by legal and illegal elite factions, this rural agency is directed primarily towards the municipal and community level. It is framed around the defence of territory and emerges on the basis of local meanings and practices. By analysing the case of an organizational process promoted by indigenous communities in Guatemala's northern highlands, I argue for paying attention to these organizational patterns despite their limited geographical projection. I derive the importance of this collective agency from their attempts to transcend a purely antagonistic stance by reconfiguring local political interactions and making their immediate surroundings more democratic.